Prevalence and Antibiotic Sensitivity Pattern of Asymptomatic Bacteriuria among Female Students and Staff of College of Applied Medical Sciences, Taif University. - Saber, Taisir; Hawsawi, Nahed M.; alharthi, Aisha hassen; algethami, Mashael hamad; alnefaie, Reem Abdullah; asiri, Aisha abdul Rahman; Saber, Tamer (Jour Med Resh and Health Sci, 2020)
Background: Asymptomatic bacteriuria (ASB) is a common condition where bacteria are present in a significant count in urine without symptoms. Pathogen persistence for a long period of time can cause urinary tract infection (UTI) that may lead to a serious complication. This study was carried out to assess the prevalence of ASB among female student and staff in College of Applied Medical Sciences, Taif university. Methods: This was a cross sectional study where a clean-catch midstream urine specimens were collected from 50 participant; 29 staff (group A) and 21 students (group B). The urine specimens were cultured quantitatively onto CLED agar plates and incubated at 35-37 ºC for 24- 48 hours. Bacterial growth equal to or more than 105 CFU/ml was considered significant. Bacteria that grew in significant count were identified by Gram stain, catalase test, coagulase test and novobiocin sensitivity. Results: Out of the 50 urine specimens screened for ASB, two specimens (4 %) showed significant bacterial growth; where one specimen (3.4 %) in group A and one specimen (4.8 %) in group B showed significant bacterial growth. The rest of urine specimens showed either no or non-significant bacterial growth. Staphylococcus saprophyticus and Staphylococcus epidermidis were the isolated organisms. Conclusion: Low prevalence of asymptomatic bacteriuria was noted in this study. This may be due to the relatively small number of the students and staff investigated. Another likely explanation is that our target group has high educational status as socioeconomic marker.